2002
DOI: 10.1002/jat.871
|View full text |Cite
|
Sign up to set email alerts
|

Haematological, hepatic and renal alterations after repeated oral or intraperitoneal administration of monoisoamyl DMSA. I. Changes in male rats

Abstract: Monoisoamyl 2,3-dimercaptosuccinic acid (MiADMSA), a vicinal thiol chelator, is gaining recognition recently as a better chelator than meso 2,3-dimercaptosuccinic acid (DMSA) in decreasing heavy metal burden in tissues because of its lipophilic character. There is, however, little information available on the toxicological properties of this chelator after repeated administration in animals. In the present study, we investigated the dose-dependent effect of MiADMSA on various biochemical parameters suggestive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…This may be due to thrombocytopenia and thrombocytosis after chronic lead intoxication (Sudakova et al, 1983;Mugahi et al, 2003;Abdulkareem, 2010); while the insignificant increase in the white blood cell may be due to lead induced inflammation (Yagminas et al, 1990, Alwaleedi, 2015.Significant increase in ALT and AST which are biomarkers for liver toxicity was observed in this study (P<0.05), might be due to increased cell membrane permeability, increased cellular basal metabolic rate or cell membrane damage of hepatocytes caused by lead acetate. These results agree with previous studies reported an elevation in AST and ALT levels after treatment with lead due to acute hepatitis, jaundice, and liver cirrhosis in mice, human and rat (Mehta et al, 2002;Patil et al, 2007;Shalan et al, 2005, Alwaleedi, 2015, also in sheep (Badiei et al, 2009). The significant decrease in albumin at the reparatory phase E3 J. Med.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to thrombocytopenia and thrombocytosis after chronic lead intoxication (Sudakova et al, 1983;Mugahi et al, 2003;Abdulkareem, 2010); while the insignificant increase in the white blood cell may be due to lead induced inflammation (Yagminas et al, 1990, Alwaleedi, 2015.Significant increase in ALT and AST which are biomarkers for liver toxicity was observed in this study (P<0.05), might be due to increased cell membrane permeability, increased cellular basal metabolic rate or cell membrane damage of hepatocytes caused by lead acetate. These results agree with previous studies reported an elevation in AST and ALT levels after treatment with lead due to acute hepatitis, jaundice, and liver cirrhosis in mice, human and rat (Mehta et al, 2002;Patil et al, 2007;Shalan et al, 2005, Alwaleedi, 2015, also in sheep (Badiei et al, 2009). The significant decrease in albumin at the reparatory phase E3 J. Med.…”
Section: Discussionsupporting
confidence: 92%
“…Taubeneck et al showed that the developmental toxicity of DMSA is mediated mainly through disturbed copper metabolism and this may also be true for MiADMSA 72) . Recently, our group was the first to report the toxicological data on MiADMSA when administered in male and female rats 73,74) through the oral as well as the intraperitoneal route (25, 50 and 100 mg/kg/3 wk). We observed that there was no major alteration in the heme biosynthesis pathway except for a slight rise in the zinc protoporphyrin levels, suggesting mild anemia at the highest dose.…”
Section: Monoisoamyl Dmsa (Miadmsa)mentioning
confidence: 99%
“…MiADMSA was seen to be slightly more toxic in terms of copper loss and some biochemical variables in the hepatic tissue of females as compared to male rats. The studies concluded that the administration of MiADMSA to female rats is confounded with side effects and may require caution during its use 73,74) . Since administration of chelating agents during pregnancy always requires caution, we studied the effects of MiADMSA administration from day 14 of gestation to day 21 of lactation at different doses through oral and ip routes to examine the maternal and developmental toxicity in the pups 75) .…”
Section: Monoisoamyl Dmsa (Miadmsa)mentioning
confidence: 99%
“…or p.o. 5 days a week for 3 weeks (Mehta et al, 2002). The MiADMSA was dissolved in sodium bicarbonate solution and the solutions were prepared immediately before use.…”
Section: Experimental Chemicals and Reagentsmentioning
confidence: 99%
“…or oral (p.o.) administration in male rats and observed that the higher doses could lead to moderate hepatotoxicity, signs of oxidative stress and significant loss of copper (Mehta et al, 2002). It is well known that the toxicity of chemicals may vary according to gender, thus we planned to study the effects of MiADMSA on parameters indicative of changes in haem biosynthesis, liver and kidney tissues and the concentration of essential metal in blood and soft tissues of female rats.…”
Section: Introductionmentioning
confidence: 99%